Development of an Android-Based Online Attendance System for Individual Service Providers of the Jagakarsa Fire Department Using the AppSheet Platform(Case Study: South Jakarta Jagakarsa Fire Department Sector) - Anwar, Octaviansyah Primadani; Rakryan, Ryan; Faizah, NM (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The study develops an Android-based Online Attendance System for the Penyedia Jasa Lainnya Perorangan (PJLP) members of the Jagakarsa Fire Department using the AppSheet platform. The project responds to long-standing issues in manual attendance management, such as time delays, data inaccuracy, and administrative inefficiency. Employing an applied research design that integrates experimental and qualitative methods, the system was developed through stages of analysis, design, implementation, and testing using the System Development Life Cycle (SDLC) framework. AppSheet and Google Sheets were utilized to create a lightweight, real-time synchronization platform without extensive programming requirements. Testing results showed a 100% success rate across functional scenarios and revealed significant improvements in reporting speed, accuracy, and user satisfaction. The system reduced report generation time by 95% and increased data accuracy to 99%. Beyond technical performance, the research also highlights the system’s influence on promoting transparency and discipline among personnel. The findings indicate that no-code platforms such as AppSheet can effectively support digital transformation in public service institutions by offering accessible, scalable, and cost-efficient technological solutions. The study concludes that integrating low-code and cloud-based tools can enhance accountability and operational effectiveness in government organizations, while future research is encouraged to expand the system’s integration, security, and behavioral impact assessment.